PENGARUH PENGGUNAAN STRATEGI INKUIRI BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS CERITA FABEL SISWA KELAS VII SMP NEGERI 34 PADANG - Nofalia, Lisa; Afnita, Afnita; Hafrison, Mohammad (Universitas Negeri Padang, 2018)
ABSTRACT This article was written to describe the effect of using au-inquired media-based inquiry strategy to the writing skills of fifteenth-grade textbook students of SMP Negeri 34 Padang. This research is a quantitative research with experimental method. The sample in this study amounted to 32 people. The data of this research is the score of skill test result of fable story writing. Based on data analysis and discussion, the following three things are concluded. First, the skills of writing fable stories without using audiovisual audiovisual media aided in VII SMP Negeri 34 Padang is in the Qualification More than Enough (Ldc) with an average score of 72.92. Second, the skill of writing fable stories using audiovisual audiovisual aided media inquiry strategy VII students of SMP Negeri 34 Padang is in Good qualification (B) with an average score of 84.11. Third, the skill of writing fable stories using audiovisual audiovisual media aided in VII SMP 34 Padang is higher than without using the audiovisual audiovisual auxiliary media strategy of VII students of SMP Negeri 34 Padang, but has not reached KKM. In other words, an audiovisual-aided audiovisual media inquiry strategy of VII students of SMP Negeri 34 Padang influences the writing skills of fifteenth-grade textbook students of SMP Negeri 34 Padang. Kata kunci: Pengaruh; Strategi Inkuiri; Media Audiovisual; Keterampilan Menulis; Teks Cerita Fabel